Pilot Study to Evaluate Hearing Aid Service Delivery Model and Measure Benefit Using Self-Report Outcome Measures Using Community Hearing Workers in a Developing Country. (6th February 2013) - Emerson, Lingamdenne Paul; Job, Anand; Abraham, Vinod
Abstract : Hearing loss is a major handicap in developing countries with paucity of trained audiologists and limited resources. In this pilot study trained community health workers were used to provide comprehensive hearing aid services in the community. One hundred and eleven patients were fitted with semi-digital hearing aid and were evaluated over a period of six months. They were assessed using self-report outcome measure APHAB. Results show that trained CHWs are effective in detecting disabling hearing loss and in providing HAs. APHAB can identify and pick up significant improvements in communication in daily activities and provides a realistic expectation of the benefits of a hearing aid. The model of using trained CHWs to provide rehabilitative services in audiology along with self-report outcome measures can be replicated in other developing countries.